Treatment of masseteric hypertrophy with botulinum toxin: A report of two cases - KÜTÜK, NÜKHET; Bas, Burcu; Ozan, Bora; Muglali, Mehtap; Celebi, Nükhet (My University, 2010)
Masseter muscle hypertrophy is a rare condition of unknown cause which is important in the differential diagnosis of head and neck masses, located in the cheek. Several treatment options reported for masseter hypertrophy, which range from simple pharmacotherapy to more invasive surgical reduction. Botulinum toxin type A is a powerful neurotoxin which is produced by the anaerobic organism Clostridium botulinum and when injected into a muscle causes interference with the neurotransmitter mechanism producing selective paralysis and subsequent atrophy of the muscle. Injection of botulinum toxin type A into the masseter muscle is generally considered a less invasive modality and has been advocated for cosmetic sculpting of the lower face. Botulinum toxin type A injection is considered to be a beneficial treatment modality in masseter muscle hypertrophy patients. The aim of this article is to report two cases of masseteric muscle hypertrophy which were treated with botulinum toxin type A injection. Marked changes in facial feature were achieved 3 months after the procedure.